Proceedings of Asia Pacific Computer Systems Conference 2021 APCS 2021 - Gokhale, Anu.; Grant, Emanuel (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book contains select proceedings papers from the Asia Pacific Computer Systems Conference (APCS 2022). The contents focus on the design and implementation of languages, data models, process models, algorithms, software and hardware for information systems. The chapters also include contributions on data mining and knowledge discovery addressing detailed descriptions of significant applications. This book proves a valuable resource for those in academia and industry interested in computational intelligence, artificial intelligence and automation.
Artificial intelligence & data science -- Computer science, database management systems -- Data mining, modelling, warehousing -- Intelligent systems & optimization -- Data management & analytics -- Data science applications in biomedicine, engineering -- Business intelligence -- Process modelling -- Human-machine collaborative systems -- Pervasive sensing & systems -- Multimedia information systems & technology. .
Keywords: Computational intelligence; Artificial intelligence; Human-machine systems; Automation; Computational Intelligence; Artificial Intelligence; Human-Machine Interfaces; Automation